Financing of local governments' cultural activities : chances and threats in Polish legal system after the year 1991 - Przybylska, Joanna (Economics and Business Review, 2007)
The systemic transformation taking place in Poland since 1989 has had a major influence on the role of culture in local communities. The times when cultural and economic policies were formulated exclusively by the state and cultural institutions were totally state-dependent ended at the beginning of the nineties when a number of economic and social reforms was introduced. The author of this article attempts to answer the questions concerning the following issues: the advantages and disadvantages of the system of financing the local cultural institutions' activities, the limitations of the system, which result in the fact that the cultural institutions are not provided with sufficient resources to finance their activities, or with possible solutions to ensure them greater independence in decision making. (original abstract)